Patient Reported Outcomes in Microbial Keratitis. Issue 1 (January 2021) - Tuohy, Megan M.; Niziol, Leslie M.; I. Mian, Shazhad; Ballouz, Dena; Bosch, David; Woodward, Maria A.
Abstract : Purpose: The aim of this investigation was to study the patient-reported outcomes of patients with microbial keratitis (MK) using the 9-item National Eye Institute-Visual Function Questionnaire (NEI VFQ-9). Methods: Using the Sight Outcomes Research Collaborative ophthalmology electronic health record repository, patients with MK and control patients who completed the NEI VFQ-9 within 7 days of their appointment were identified. The questionnaire is scored as a mean of the 9 items on a scale from 0 to 100, with higher scores indicating better functioning. Composite and individual item scores were compared between groups using the analysis of variance. Results: In total, 916 questionnaires were completed from patients with acute MK (n = 84), nonacute MK (n = 30), MK with a corneal transplant (n = 21), from controls seen in a satellite comprehensive ophthalmology clinic (n = 528), and controls seen at a subspecialty ophthalmology clinic (n = 253). The mean NEI VFQ-9 composite scores per group were 66.6 (SD = 26.8), 78.1 (SD = 17.1), 58.6 (SD =21.6), 88.0 (SD = 10.2), and 83.5 (SD = 13.0), respectively ( P < 0.0001). Both patients with acute MK and patients with MK requiring transplant reported significantly worse function than nonacute MK, comprehensive, and specialty patients. Patients with nonacute MK reported significantly worse function than comprehensive control patients (all Tukey-adjusted P < 0.05). Discussion: Patients who had or eventually require corneal transplant for management of their MK report worse visual function than patients with nonacute MK. This may be important in helping physicians counsel their patients.